2013
DOI: 10.3762/bjoc.9.190
|View full text |Cite
|
Sign up to set email alerts
|

Bromination of hydrocarbons with CBr4, initiated by light-emitting diode irradiation

Abstract: SummaryThe bromination of hydrocarbons with CBr4 as a bromine source, induced by light-emitting diode (LED) irradiation, has been developed. Monobromides were synthesized with high efficiency without the need for any additives, catalysts, heating, or inert conditions. Action and absorption spectra suggest that CBr4 absorbs light to give active species for the bromination. The generation of CHBr3 was confirmed by NMR spectroscopy and GC–MS spectrometry analysis, indicating that the present bromination involves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…To avoid the complexity of having compounds bearing different halogens in the reaction mixture, the reaction was repeated in dichloromethane using CCl 4 as the reagent, instead of CBr 4 ( Table 1 , entry 2). Although we had no evidence of light-sensitivity, we conducted this and all future experiments in foil-covered flasks [ 19 ]. The reaction yielded (2,2-dichloro-1-methylcyclopropyl)-benzene 19 as the major product.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the complexity of having compounds bearing different halogens in the reaction mixture, the reaction was repeated in dichloromethane using CCl 4 as the reagent, instead of CBr 4 ( Table 1 , entry 2). Although we had no evidence of light-sensitivity, we conducted this and all future experiments in foil-covered flasks [ 19 ]. The reaction yielded (2,2-dichloro-1-methylcyclopropyl)-benzene 19 as the major product.…”
Section: Resultsmentioning
confidence: 99%
“…As in Nishina's study, [16] irradiation of CBr 4 promotes the homolytic cleavage of a C-Br bond to produce an electrophilic radical, · CBr 3 . As proposed by Stephenson, [11] 3+ is reduced to its original oxidation state by using a sacrificial electron donor such as R 3 N. A control experiment in which trialkylamine was removed for the second irradiation showed no formation of dehalogenated product; this demonstrated that the iPrOH/DMF solvent mixture did not participate in background reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Under visible light irradiation, the metal‐free CBr 4 produces radicals by homolytic cleavage of the C−Br bond; and these active radicals could initiate a couple of oxidation or bromination reactions . It is reasonable to expect the activation of the sp 3 C−H bond adjacent to an amino group by oxidation, which could be thereafter coupled with alcohol in the nucleophilic addition reaction to form hemiaminal functional motif.…”
Section: Figurementioning
confidence: 99%
“…Based on the experimental facts, a tentative reaction mechanism is proposed. As shown in Scheme a, CBr 4 has weak visible light absorbance, and under visible light irradiation, CBr 4 generates bromine radical and tribromomethyl radical by homolytic cleavage. The tribromomethyl radical could further release one more bromine radical and dibromocarbene, which is evidenced by the carbene coupling product (tetrabromoethylene).…”
Section: Figurementioning
confidence: 99%